Dietary inflammatory potential is associated with higher odds of hepatic steatosis in US adults: a cross-sectional study - Hu Yang; Tengfei Zhang; Wen Song; Zhaohong Peng; Yu Zhu; Yong Huang; Xiude Li; Zhuang Zhang; Min Tang; Wanshui Yang (Cambridge University Press, 2023)
Abstract Objective: Inflammation plays a critical role in the progression of chronic liver diseases, and diet can modulate inflammation. Whether an inflammatory dietary pattern is associated with higher risk of hepatic steatosis or fibrosis remains unclear. We aimed to investigate the associations between inflammatory dietary pattern and the odds of hepatic steatosis and fibrosis. Design: In this nationwide cross-sectional study, diet was measured using two 24-h dietary recalls. Empirical dietary inflammatory pattern (EDIP) score was derived to assess the inflammatory potential of usual diet, which has been validated to highly predict inflammation markers in the study population. Controlled attenuation parameter (CAP) and liver stiffness measurement (LSM) were derived from FibroScan to define steatosis and fibrosis, respectively. Setting: US National Health and Nutrition Examination Survey. Participants: 4171 participants aged ≥18 years. Results: A total of 1436 participants were diagnosed with S1 steatosis (CAP ≥ 274 dB/m), 255 with advanced fibrosis (LSM ≥ 9·7 kPa). Compared with those in the lowest tertile of EDIP-adherence scores, participants in the highest tertile had 74 % higher odds of steatosis (OR: 1·74, 95 % CI (1·26, 2·41)). Such positive association persisted among never drinkers, or participants who were free of hepatitis B and/or C. Similarly, EDIP was positively associated with CAP in multivariate linear model (P < 0·001). We found a non-significant association of EDIP score with advanced fibrosis or LSM (P = 0·837). Conclusions: Our findings suggest that a diet score that is associated with inflammatory markers is associated with hepatic steatosis. Reducing or avoiding pro-inflammatory diets intake might be an attractive strategy for fatty liver disease prevention.